(untitled) (Dhaka University Journal of Biological Sciences, 2016)
This study was carried out to explore the level of depression among married women. Additionally, the role of employment status, academic qualification, marital satisfaction and psychological well-being on depression was examined. Depression, marital satisfaction and psychological well-being of 200 married women were assessed. Results showed 15% of the study participants scored above the cut-off point of depression and are at the risk of depression. Employment and academic status, marital satisfaction and psychological wellbeing (GHQ-28) jointly accounted for 56.2% variability in the depression with psychological well-being (β = 0.515, p < 0.001) and marital satisfaction (β = –0.276, p < 0.001) appeared as the most influential predictors. Lower education and unemployment also associated with the higher level of depression. The model indicated if a married woman with poorer psychological well-being, lower marital satisfaction and lower educational qualification is unemployed, she is more likely to be diagnosed as depressed. Implications and future direction are discussed. Dhaka Univ. J. Biol. Sci. 25(2): 113-121, 2016 (July)